2022
DOI: 10.4251/wjgo.v14.i10.2004
|View full text |Cite
|
Sign up to set email alerts
|

Multi-slice spiral computed tomography in differential diagnosis of gastric stromal tumors and benign gastric polyps, and gastric stromal tumor risk stratification assessment

Abstract: BACKGROUND The biological characteristics of gastric stromal tumors are complex, and their incidence has increased in recent years. Gastric stromal tumors (GST) have potential malignant tendencies, and the probability of transformation into malignant tumors is as high as 20%-30%. AIM To investigate the value of multi-slice spiral computed tomography (MSCT) in the differential diagnosis of GST and benign gastric polyps, and GST risk stratification assessment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…In addition, mean attenuation values on arterial phase images and peak attenuation values were greater in high-risk GISTs (78.72 ± 12.66 [SD] HU and 80.79 ± 12.37 [SD] HU, respectively) compared to the low-intermediate-risk GISTs (55.71 ± 13.77 [SD] HU, P < .001 and 72.66 ± 12.46 [SD] HU, P = .015, respectively). 46 Grazzini et al confirmed the high value of enlarged feeding or draining vessels but also that of tumor necrosis in a series of 54 patients with 56 GISTs. 57 They found that these 2 features on contrast-enhanced CT images had 89.3% accuracy (50/56 GISTs) for the diagnosis of high-risk GISTs.…”
Section: Risk Stratification and Survival Predictionmentioning
confidence: 86%
See 3 more Smart Citations
“…In addition, mean attenuation values on arterial phase images and peak attenuation values were greater in high-risk GISTs (78.72 ± 12.66 [SD] HU and 80.79 ± 12.37 [SD] HU, respectively) compared to the low-intermediate-risk GISTs (55.71 ± 13.77 [SD] HU, P < .001 and 72.66 ± 12.46 [SD] HU, P = .015, respectively). 46 Grazzini et al confirmed the high value of enlarged feeding or draining vessels but also that of tumor necrosis in a series of 54 patients with 56 GISTs. 57 They found that these 2 features on contrast-enhanced CT images had 89.3% accuracy (50/56 GISTs) for the diagnosis of high-risk GISTs.…”
Section: Risk Stratification and Survival Predictionmentioning
confidence: 86%
“…2,[43][44][45] One study involving 124 patients (64 with GISTs and 60 with benign gastric polyp) who underwent CT examination, found that extraluminal growth (50%; 32/64), irregular margins (83%; 53/64) and tumour ulceration (28%; 18/64) were more frequently observed in gastric GISTs than in benign gastric polyps (10 [6/60]; 33% [20/ 60]; and 7% [4/60], respectively) (P < .001, <.001 and .002, respectively). 46 Similarly, GISTs showed greater degrees of enhancement during the arterial phase compared to benign gastric polyps. 46 In this study, the best capabilities for tumour discrimination were obtained using semantic features (area under the curve [AUC], .784) rather than using attenuation values on arterial phase images (AUC, .710) or peak attenuation values (AUC, .710).…”
Section: Lesion Characterizationmentioning
confidence: 97%
See 2 more Smart Citations